Perlindungan Hukum Tenaga Kerja terhadap Pelaksanaan Jaminan Kecelakaan Kerja di PT. Hiruta Kogyo Indonesia - Akhwil, Zainul; S, Imam Budi (Wajah Hukum, 2023)
Labor Law Protection for the Implementation of Work Accident Insurance at PT. Hiruta Kogyo Indonesia. The first goal of this research is to comprehend how PT. Hiruta Kogyo Indonesia has implemented legal protection for occupational safety and health. The second goal is to comprehend if PT. Hiruta Kogyo Indonesia has clear laws on methods for guarantee of occupational safety and health. This investigation, which is empirical in nature, was carried out by PT. Hiruta Kogyo Indonesia. The data collection method makes use of field research and interviewing methods. Qualitative analysis methods are used to assess both primary and secondary data. The findings of this study demonstrate that (1) Occupational Safety and Health at PT. Hiruta Kogyo Indonesia has been implemented based on the K3 management system, (2) Legal Protection of Work Accident Cases at PT. Hiruta Kogyo Indonesia is a top priority by being given health insurance, and (3) Regulations that ensure occupational safety and health for workers have been implemented. Program Implementation (K3) and SMK3 Implementation are the rules in dispute.